2012
DOI: 10.1200/jco.2011.38.9791
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among 5-Year Survivors of Esophageal Cancer Surgery: A Prospective Population-Based Study

Abstract: HRQL recovers to a level comparable to that in the background population in most patients who survive 5 years after esophagectomy for cancer, although a subgroup of patients has substantially worse HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
120
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 23 publications
9
120
2
Order By: Relevance
“…Eating difficulties, pain, fatigue, nausea and vomiting, and appetite loss were clinically relevant and statistically significant worse symptoms experienced among those with a post-operative weight loss [7] . Our results are in line with studies which report that approximately 3 months after esophagectomy, patients report worse functional aspects of QOL (physical, social, role and cognitive function) and more problems with fatigue, nausea and vomiting, pain, appetite loss, diarrhea, dry mouth and loss of taste than before treatment [5][6][7][8][9] . With the goal of improving postoperative outcomes, there has been a trend towards the increased use of trimodality therapy (induction chemotherapy and radiation therapy, followed by surgery) and minimally invasive esophagectomy (MIE) for esophageal resection; although their advantages and cost effectiveness remains debatable [10,11] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eating difficulties, pain, fatigue, nausea and vomiting, and appetite loss were clinically relevant and statistically significant worse symptoms experienced among those with a post-operative weight loss [7] . Our results are in line with studies which report that approximately 3 months after esophagectomy, patients report worse functional aspects of QOL (physical, social, role and cognitive function) and more problems with fatigue, nausea and vomiting, pain, appetite loss, diarrhea, dry mouth and loss of taste than before treatment [5][6][7][8][9] . With the goal of improving postoperative outcomes, there has been a trend towards the increased use of trimodality therapy (induction chemotherapy and radiation therapy, followed by surgery) and minimally invasive esophagectomy (MIE) for esophageal resection; although their advantages and cost effectiveness remains debatable [10,11] .…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that in esophageal cancer, the quality of life rapidly deteriorates in most patients, due to disease-related symptoms such as dysphagia, pain, fatigue, appetite loss and constipation before treatment [5] . It has been documented that advances in surgical technique and post-operative care have considerably improved short come outcomes [6] .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the majority of the patients who survived esophageal surgery to the 5-year mark recovered to HRQOL levels comparable to the background, general population (30). Physical function was either stable or improved in 86% of patients, to a level which was similar to the general population (30). However, there was a subgroup of patients (14%) that deteriorated substantially globally (30).…”
Section: Postoperative Hrqolmentioning
confidence: 99%
“…Derogar and Lagergren, in their 2012 prospective population-based cohort study, examined HRQOL in patients at 6 months, 3 and 5 years post esophagectomy using self-administered EORTC QLQ-C30 version 3.0 and EORTC QLQ-OES18 module (30). They compared HRQOL in esophageal cancer patients to age-and sex-matched general population (30).…”
Section: Postoperative Hrqolmentioning
confidence: 99%
See 1 more Smart Citation